Empowering Patients to Self-Manage Common Infections: Qualitative Study Informing the Development of an Evidence-Based Patient Information Leaflet - Catherine V. Hayes; Bláthnaid Mahon; Eirwen Sides; Rosie Allison; Donna M. Lecky; Cliodna A. M. McNulty (MDPI AG, 2021)
Common self-limiting infections can be self-managed by patients, potentially reducing consultations and unnecessary antibiotic use. This qualitative study informed by the Theoretical Domains Framework (TDF) aimed to explore healthcare professionals' (HCPs) and patients' needs on provision of self-care and safety-netting advice for common infections. Twenty-seven patients and seven HCPs participated in semi-structured focus groups (FGs) and interviews. An information leaflet was iteratively developed and reviewed by participants in interviews and FGs, and an additional 5 HCPs, and 25 patients (identifying from minority ethnic groups) via online questionnaires. Qualitative data were analysed thematically, double-coded, and mapped to the TDF. Participants required information on symptom duration, safety netting, self-care, and antibiotics. Patients felt confident to self-care and were averse to consulting with HCPs unnecessarily but struggled to assess symptom severity. Patients reported seeking help for children or elderly dependents earlier. HCPs' concerns included patients' attitudes and a lack of available monitoring of advice given to patients. Participants believed community pharmacy should be the first place that patients seek advice on common infections. The patient information leaflet on common infections should be used in primary care and community pharmacy to support patients to self-manage symptoms and determine when further help is required.